In concentration dependence of shallow ımpurity binding energy under the hydrostatic pressure - Başer, Pınar; Altuntaş, Ismail; Elagöz, Sezai (Marmara Üniversitesi Fen Bilimleri Dergisi, 2011)
The ground state binding energy of axial hydrogenic impurity in zinc-blende (ZB) InxGa1-xN/GaN cylindrical quantum well wires( CQWWs) are investigated as a function of the In concentration and the radius of the wire under hydrostatic pressure in the effective mass approximation and variational calculation scheme. The effect of applied hydrostatic pressure is introduced into the calculations using pressure dependent values of energy band gap and effective mass. Numerical results show that the ground-state shallow impurity binding energy Eb altered when both the hydrostatic pressure and In concentration increases for an on-center impurity. We have found that for large radii the binding energies are not affected by applied pressure. However, in the region where the particles interact with the barrier the binding energy is strongly dependent on the hydrostatic pressure for all x values. Furthermore, we have seen that the binding energy of the shallow impurity is affected more by the change of In concentration compared to the change of hydrostatic pressure.
Keywords: Quantum wires; Binding energy; Hydrostatic pressure; In concentration